2005
DOI: 10.1016/j.bbamem.2005.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid diversity: Correlation with membrane–membrane fusion events

Abstract: The transport of various metabolically important substances along the endocytic and secretory pathways involves budding as well as fusion of vesicles with various intracellular compartments and plasma membrane. The membrane-membrane fusion events between various sub-compartments of the cell are believed to be mainly mediated by so-called "fusion proteins". This study shows that beside the proteins, lipid components of membrane may play an equally important role in fusion and budding processes. Inside out (ISO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The lipid mixing assay confirmed that the interaction between liposomes and bacteria is fusion while ruling out the possibility of adsorption or aggregation (6,44). Based on the assay's principle, fusion of fluorescent vesicles to nonfluorescent lipids, i.e., bacterial cells, results in probe dilution and a decrease in resonance energy transfer efficiency due to an increase in distance between NDB-PE and Rh-PE (40).…”
Section: Discussionmentioning
confidence: 90%
“…The lipid mixing assay confirmed that the interaction between liposomes and bacteria is fusion while ruling out the possibility of adsorption or aggregation (6,44). Based on the assay's principle, fusion of fluorescent vesicles to nonfluorescent lipids, i.e., bacterial cells, results in probe dilution and a decrease in resonance energy transfer efficiency due to an increase in distance between NDB-PE and Rh-PE (40).…”
Section: Discussionmentioning
confidence: 90%
“…Phosphatidylethanolamine, which is the most abundant lipid on the cytoplasmic layer of cellular membranes, plays significant roles in cellular processes such as membrane fusion [17], cell cycle [18], autophagy [19], apoptosis [20], and cognitive function [21]. Three main biochemical pathways are recognized for production of phosphatidylethanolamine; CDP-ethanolamine Kennedy pathway, mitochondrial phosphatidylserine decarboxylation pathway catalyzed by phosphatidylserine decarboxylase, and acylation of lysophosphatidylethanolamine catalyzed by lysophosphatidylethanolamine acyltransferase.…”
Section: Discussionmentioning
confidence: 99%
“…PE is the most abundant lipid on the cytoplasmic layer of cellular membranes, with significant roles in cellular processes such as membrane fusion [54], cell cycle [55], autophagy [56], and apoptosis [57]. The phosphatidylethanolamine ranges from 1.13 in small alligator peppers to 558.00 mg/100 g in malaba spinach.…”
Section: Overview Of the Phospholipids Composition Of Nigerian Vegetamentioning
confidence: 99%